2005
DOI: 10.5558/tfc81710-5
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of climate change risk to forest ecosystems and forest-based communities

Abstract: Perception of risk or subjective risk is playing an increasingly important role in risk assessment. This paper describes a study that investigated perceptions of climate change risk to forest ecosystems and forest-based communities among a sample of Canadian forestry experts. Data were collected by questionnaire from participants at a climate change and forestry workshop, sponsored by the Canadian Climate Impacts and Adaptation Research Network Forest Sector and the McGregor Model Forest held in Prince George,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 15 publications
3
44
2
2
Order By: Relevance
“…This proportion rises to 86% when future impacts (2050) are considered. These results show that in Quebec, in contrast with the situation reported in British Columbia (Williamson et al 2005), forest practitioners are reported as being more sensitive to future climate impacts than to current ones. In comparison with BC practitioners, Quebec foresters have not been as exposed to CC impacts as catastrophic as the mountain pine beetle outbreak, which may explain the difference in perceptions between the two provinces.…”
Section: Main Perceptions About Climate Changecontrasting
confidence: 61%
“…This proportion rises to 86% when future impacts (2050) are considered. These results show that in Quebec, in contrast with the situation reported in British Columbia (Williamson et al 2005), forest practitioners are reported as being more sensitive to future climate impacts than to current ones. In comparison with BC practitioners, Quebec foresters have not been as exposed to CC impacts as catastrophic as the mountain pine beetle outbreak, which may explain the difference in perceptions between the two provinces.…”
Section: Main Perceptions About Climate Changecontrasting
confidence: 61%
“…Increased frequency and intensity of forest fires would have severe consequences not only for rural communities dominated by commercial tree plantations but also the South African forestry sector, which contributes about 2 per cent of the country's gross domestic product (GDP) (Williamson et al, 2005;Chamberlain et al, 2005). According to FSA (2009), fire is one of the major risks that negatively affect the sustainability of plantation forests in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Wesche et al 2006 for a temperate example). A study along the lines of Williamson et al (2005) aimed at assessing the perceptions of climate change risk in temperate forests could be useful in the context of tropical forestry by helping to formulate future management options and policy development at the national or local level.…”
Section: Institutional and Policy Approachesmentioning
confidence: 99%